Single- and double-hit events in genes encoding immune targets before and after T cell-engaging antibody therapy in MM - Truger, Marietta; Duell, Johannes; Zhou, Xiang; Heimeshoff, Larissa; Ruckdeschel, Anna; John, Mara; Riedel, Angela; Hüper, Sebastian; Peter, Jessica; Walter, Wencke; Haertle, Larissa; Meggendorfer, Manja; et al. (Blood advances, 2021)
T cell-engaging immunotherapies exert unprecedented single-agent activity in multiple myeloma (MM), thereby putting a yet unexplored selective pressure on the clonal architecture. In this study, we report on homozygous BCMA (TNFRSF17) gene deletion after BCMA-targeting T cell-redirecting bispecific antibody therapy in a heavily pretreated MM patient. Loss of BCMA protein expression persisted over subsequent relapses, with no response to treatment with anti-BCMA antibody drug conjugate. In light of the multiple alternative targets that are emerging in addition to BCMA, we extended our analyses to delineate a more complete picture of genetic alterations that may have an impact on immunotherapy targets in MM. We performed whole-genome sequencing and RNA sequencing in 100 MM patients (50 were newly diagnosed; 50 were relapsed/refractory) and identified a significant proportion of patients with aberrations in genes encoding immunotherapy targets; GPRC5D ranked first with 15% heterozygous deletions, followed by CD38 (10%), SDC1 (5%), and TNFRSF17 (4%). Notably, these heterozygous deletions did not lower the expression levels of respective genes, but they may represent a first hit that drives the acquisition of homozygous deletions and subsequent antigen-loss relapse upon targeted immunotherapy. In summary, we show preexisting vulnerability in genes encoding immunotargets before and homozygous deletions after T cell-engaging immunotherapy.
Gesehen am 09.02.2022